2015
DOI: 10.5603/kp.a2015.0090
|View full text |Cite
|
Sign up to set email alerts
|

The effect of statin treatment on P-wave characteristics and atrial conduction time

Abstract: A b s t r a c t Background and aim:The aim of this study was to evaluate the effect of statin treatment on P-wave morphology, dispersion, and tissue Doppler imaging-derived atrial conduction time (PA-TDI), which are known to be predictors of atrial fibrillation (AF). Methods:A total of 132 patients with guideline-directed statin indications but no clinical atrial tachyarrhythmias were studied. P-wave duration, P-wave dispersion, and P-wave amplitude on surface 12-lead electrocardiogram and PA-TDI were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The mechanisms by which statins reduce mortality in AF-related stroke are related to their pleiotropic effects on the cardiovascular and endocardial circulatory systems [ 47 , 48 ]. Statins have also been found to improve left ventricular function, reduce levels of interleukin-6 and C-reactive protein, increase nitric oxide bioavailability, increase antioxidant properties, and inhibit inflammatory response and plaque stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which statins reduce mortality in AF-related stroke are related to their pleiotropic effects on the cardiovascular and endocardial circulatory systems [ 47 , 48 ]. Statins have also been found to improve left ventricular function, reduce levels of interleukin-6 and C-reactive protein, increase nitric oxide bioavailability, increase antioxidant properties, and inhibit inflammatory response and plaque stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…Our results underline the dynamics of myocardial remodelling after ASD closure. Increased PWD (> 40 ms) was reported to have a significant influence on the risk of AF development, both idiopathic and associated with diseases influencing cardiovascular function [23][24][25]. Numerous experimental and clinical studies have shown that AF/atrial flutter in heart defects (including Figure 1.…”
Section: Discussionmentioning
confidence: 99%